2006
DOI: 10.1159/000097464
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Is Associated with Increased Overall Survival in Patients with Multiple Myeloma

Abstract: Background: Recombinant human erythropoietin (rhEPO) is effective for the treatment of anemia associated with multiple myeloma. Data from animal studies and case reports suggest that rhEPO has antineoplastic properties. Methods: Two hundred and ninety-two patients enrolled on different chemotherapy clinical trials at the Cleveland Clinic Myeloma Program between 1997 and 2003 were the subjects of this study. Information on erythropoietin use as well as baseline prognostic variables were collected retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…These studies were led by the observation that multiple myeloma (MM) patients treated with rHuEPO for their anemia, exhibited prolonged survival and improved quality of life (Baz et al, 2007;Mittelman et al, 1997;Mittelman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These studies were led by the observation that multiple myeloma (MM) patients treated with rHuEPO for their anemia, exhibited prolonged survival and improved quality of life (Baz et al, 2007;Mittelman et al, 1997;Mittelman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from these authors indicated that EPO may prolong survival in MM patients [8], and these results have been supported by other scientists [9]. The effect of EPO on MM was also reproduced in murine models, where EPO promotes the development of an effective and long-lasting anti-tumor specific immune response mediated via activated CD8 + T cells [10].…”
mentioning
confidence: 62%
“…Epo use was associated with significantly reduced myeloma survival in one retrospective study, 2 whereas other studies showed that Epo caused myeloma regression in mice, 3 that Epo did not impair time to progression or overall survival in patients treated with melphalan and prednisone with or without bortezomib, 4 or that Epo improved survival. 5 Whether tumor epithelial and/or endothelial cells express functional Epo receptor (EpoR) is the subject of controversy. 6 The ability to unequivocally link tumor EpoR expression with Epo treatment and clinical outcomes would provide a means for directly testing the clinical significance of tumor EpoR expression.…”
Section: Evaluating Surface Erythropoietin Receptor In Multiple Myelomamentioning
confidence: 99%
“…Error bars represent the average deviation of duplicate determinations. (b) Staining with FAB307P or A82 plus a secondary PE antibody (red histograms), or the corresponding isotype controls (blue histograms) is shown in plasma cells from the bone marrow of patients with multiple myeloma (patients [1][2][3][4][5][6][7][8] or normal donors (N1-N3). Staining events are shown in gated plasma cells, which were identified on the basis of CD45, CD38, CD138, CD19, and CD56 expression.…”
Section: Evaluating Surface Erythropoietin Receptor In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation